Characteristics and Treatment Outcome of Pediatric Diabetic Ketoacidosis in Mekong Delta, Vietnam: A 5-Year Retrospective Study (Bangladesh Journal of Medical Science, 2024)
Background Diabetic ketoacidosis (DKA), a critical and potentially fatal complication resulting from a lack of insulin, presents with elevated blood sugar, acid-base imbalance, and increased ketone bodies. Objectives Our research was designed to assess the clinical manifestations, laboratory findings, and outcomes of treatment in children diagnosed with DKA over a span of five years in the Mekong Delta region of Vietnam. Methods This study retrospectively analyzed pediatric cases of diabetic ketoacidosis treated at a major pediatric center in the Mekong Delta between 2017 and 2021. Results Diabetic ketoacidosis was more common in older children aged 11 – 16 years (66.7%), and females (70%). The majority of cases had not been diagnosed with previous diabetes (60%) and no history of diabetic ketoacidosis (90%). In univariate analysis, female gender (OR, 13.0; 95% CI, 1.4 – 124.3; p=0.026), previous diabetes diagnosis (OR, 7.8; 95% CI, 1.5 – 41.2; p=0.016), precipitating factors (OR, 10.1; 95% CI, 1.1 – 97.0; p=0.045), tachypnea (OR, 5.5; 95% CI, 1.1 – 26.4; p=0.033), Kussmaul breathing (OR, 5.4; 95% CI, 1.1 – 26.0; p=0.036), serum potassium level (OR, 3.5; 95% CI, 1.2 – 10.4; p=0.027), and anion gap (OR, 1.6; 95% CI, 1.8 – 2.3; p=0.003) were associated factors with severe DKA. All cases in our study had a 100% survival rate. Anion gap was an independent factor associated with severe diabetic ketoacidosis after adjustment multivariate analysis. Conclusion: Female, younger age, precipitating factors, tachypnea, Kussmaul’s breathing, and relevant laboratory findings, including increased anion gap, should be considered to ensure successful management in pediatric diabetic ketoacidosis.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1112-1119